A Death in the Photo: Understanding the Korean Empire through Alma Karlin’s Black and White Photograph of the Funeral Procession in front of Daeanmun Gate - Kang, Byoung Yoong (Poligrafi, 2019)
In June 1923 Alma Karlin (1889-1950) first stepped onto the Korea peninsula at Busan. The peninsula was in turmoil, gradually occupied by Japan by means of ‘cultural rule'. From Busan, Karlin travelled through Seoul and Pyongyang before leaving to China. Like other tourists, she packed her suitcase with authentic souvenirs of Korea. There are thirty-nine photographs in total that Karlin brought from Korea to Slovenia. Five of them are funeral themed photos, and in one of the five one can discern the poignant story of a Joseonian woman’s death amid a troubled Korean Empire. The photo attracted global interest as it was exhibited not only in Korea, but Slovenia and the US. In the present paper, I scrutinise the details of the photo and attempt to deepen the understanding of early twentieth century Korea as it is observed in the photo. The paper explores one photo with a focus on historical particularities in Korea including architecture, the history of the palace, the signboard on the gate, and the relations of the royal family. It confirms a new theory regarding the image, that it is a scene from the funeral procession for Empress Sunmyeong, who died tragically as a Crown Princess during the era of the one and final Korean Empire.